Signal transduction in the activation of spermatozoa compared to other signalling pathways: a biological networks study. (2015) - Bernabò, Nicola; Mattioli, Mauro; Barboni, Barbara
In this paper we represented Spermatozoa Activation (SA) the process that leads male gametes to reach their fertilising ability of sea urchin, Caenorhabditis elegans and human as biological networks, i.e. as networks of nodes (molecules) linked by edges (their interactions). Then, we compared them with networks representing ten pathways of relevant physiopathological importance and with a computergenerated network. We have found that the number of nodes and edges composing each network is not related with the amount of published papers on each specific topic and that all the topological parameters examined are similar in all the networks, thus conferring them a scale free topology and small world behaviour. In conclusion, SA topology, independently from the reproductive biology of considered organism, as others signalling networks is characterised by robustness against random failure, controllability and efficiency in signal transmission.